Detection of serum/salivary exosomal Alix in patients with oral squamous cell carcinoma. (7th August 2020) - Nakamichi, Eiji; Sakakura, Hiroki; Mii, Shinji; Yamamoto, Noriyuki; Hibi, Hideharu; Asai, Masato; Takahashi, Masahide
Abstract: Objective: Owing to variations in the exterior appearances of noncancerous diseases in the oral cavity, clinicians may have difficulty diagnosing oral squamous cell carcinoma (OSCC). Tissue biopsy is confirmatory, but invasive. Therefore, reliable tumor markers for OSCC are required. Here, exosomal Alix (exoAlix) levels were measured in serum/salivary samples from patients with OSCC and healthy controls (HCs). Methods: Fifty‐seven patients admitted to Nagoya University Hospital from 2017 through 2019 were enrolled, and serum samples (OSCC, n = 29; HC, n = 21) and/or saliva samples (OSCC, n = 23; HC, n = 20) were collected. Exosomal fractions were isolated using ultracentrifugation. ExoAlix levels were measured using enzyme‐linked immunosorbent assay. Results: Serum/salivary exoAlix levels were significantly higher in patients with OSCC than in HCs. Receiver operating characteristic analyses revealed that sensitivity, specificity, positive predictive value, and area under the curve were 0.345, 1.000, 1.000, and 0.685, respectively, for serum exoAlix and 0.348, 1.000, 1.000, and 0.712, respectively, for salivary exoAlix at optimal cut‐off values (serum, 0.205; saliva, 0.193). All tested OSCC tissue sections ( n = 21) were immuno‐reactive for Alix. Conclusion: Serum and salivary exoAlix were identified as potential diagnostic OSCC biomarkers. Serum exoAlix was suitable for prediction of therapeutic responses.